Changes in segment coordination variability and the impacts of the lower limb across running mileages in half marathons: Implications for running injuries - Tony Lin-Wei Chen; Duo Wai-Chi Wong; Yan Wang; Qitao Tan; Wing-Kai Lam; Ming Zhang (Elsevier, 2022)
Background: Segment coordination variability (CV) is a movement pattern associated with running-related injuries. It can also be adversely affected by a prolonged run. However, research on this topic is currently limited. The purpose of this study was to investigate the effects of a prolonged run on segment CV and vertical loading rates during a treadmill half marathon. Methods: Fifteen healthy runners ran a half marathon on an instrumental treadmill in a biomechanical laboratory. Synchronized kinematic and kinetic data were collected every 2 km (from 2 km until 20 km), and the data were processed by musculoskeletal modeling. Segment CVs were computed from the angle-angle plots of selected pelvis-thigh, thigh-shank, and shank-rearfoot couplings using a modified vector coding technique. The loading rate of vertical ground reaction force was also calculated. A one-way MANOVA with repeated measures was performed on each of the outcome variables to examine the main effect of running mileage. Results: Significant effects of running mileage were found on segment CVs (p ≤ 0.010) but not on loading rate (p = 0.881). Notably, during the early stance phase, the CV of pelvis frontal vs. thigh frontal was significantly increased at 20 km compared with the CV at 8 km (g = 0.59, p = 0.022). The CV of shank transverse vs. rearfoot frontal decreased from 2 km to 8 km (g = 0.30, p = 0.020) but then significantly increased at both 18 km (g = 0.05, p < 0.001) and 20 km (g = 0.36, p < 0.001). Conclusion: At the early stance, runners maintained stable CVs on the sagittal plane, which could explain the unchanged loading rate throughout the half marathon. However, increased CVs on the frontal/transverse plane may be an early sign of fatigue and indicative of possible injury risk. Further studies are necessary for conclusive statements in this regard.